2008
DOI: 10.3382/ps.2007-00188
|View full text |Cite
|
Sign up to set email alerts
|

Slaughter Performance of Four Different Turkey Strains, with Special Focus on the Muscle Fiber Structure and the Meat Quality of the Breast Muscle

Abstract: The increase in human consumption of turkey meat and the shift in the poultry market from whole birds to further processed meat products increases the visibility of meat alterations (e.g., heterogenic color, drip loss, petechial hemorrhages) at retail. Changes in poultry meat quality have been related to the intensive growth of the current turkey strains. Considering this, the main objective of this investigation was to evaluate the meat quality and muscle structure of commercially available turkey strains wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
53
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 55 publications
10
53
2
Order By: Relevance
“…Also taking into account the results of Opalka et al (2004), which presented a higher oxidative energy metabolism in the MIL, and the present results with a higher MRA of the MG, it could be concluded that shortly after slaughter the glycogen in the MG is degraded to a higher extent via citrate cycle and ETC in comparison with the MPS accompanied with lower lactate accumulation and higher pH, as shown by Fernandez et al (2001). The EC values determined 24 h p.m. support this assumption, as this parameter is negatively correlated with the pH (Werner et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…Also taking into account the results of Opalka et al (2004), which presented a higher oxidative energy metabolism in the MIL, and the present results with a higher MRA of the MG, it could be concluded that shortly after slaughter the glycogen in the MG is degraded to a higher extent via citrate cycle and ETC in comparison with the MPS accompanied with lower lactate accumulation and higher pH, as shown by Fernandez et al (2001). The EC values determined 24 h p.m. support this assumption, as this parameter is negatively correlated with the pH (Werner et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…A comparison with other studies indicates that the analysed meat samples were characterised by satisfactory chemical composition (Werner et al, 2008;Lipiński et al, 2011;Mikulski et al, 2012). According to the panellists, turkey breast muscles were also characterised by high sensory quality and shear force values indicative of satisfactory …”
Section: Discussionmentioning
confidence: 71%
“…al., 2001; Lonergan et al, 2003;Sandercock et al, 2009) and turkey lines (Fernandez et al, 2001;Werner et al, 2008), accepting a wide range in body weight. The broilers could exploit their genetic potential for growth performance and carcass quality.…”
Section: Discussionmentioning
confidence: 99%